Sammy keyes and the hotel thief - Van Draanen, Wendelin (New York : Knopf, 1998)
Thirteen-year-old Sammy's penchant for speaking her mind gets her in trouble when she involves herself in the investigation of a robbery at the "seedy" hotel across the street from the seniors' building where she is living with her grandmother.
Keywords: Grandmothers -- Fiction; Robbers and outlaws -- Fiction; Mystery and detective stories